THE EXPERIENCE OF ORGANIZING THE HEALTH INSURANCE SYSTEM IN THE RUSSIAN FEDERATION: LEGAL, FINANCIAL, AND INSTITUTIONAL PERSPECTIVES (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the development of the compulsory health insurancesystem in the Russian Federation and analyzes its legal, institutional, and financialmechanisms. The study explores the historical evolution of the Russian healthcareinsurance model, the structure of financing, the role of federal and territorial insurancefunds, and the implementation of digital healthcare technologies. Particular attentionis paid to the challenges and achievements of the Russian model in ensuring universalhealthcare coverage. The research findings may serve as a useful reference for healthcarereforms in developing countries, including Uzbekistan.
Keywords: : compulsory health insurance; Russian Federation; healthcare financing; medical insurance; healthcare reform; universal health coverage; OMS system; Semashko model; digitalization; post-Soviet transition